2013
DOI: 10.1074/jbc.m113.501791
|View full text |Cite
|
Sign up to set email alerts
|

Structural Snapshots from the Oxidative Half-reaction of a Copper Amine Oxidase

Abstract: Background: Copper amine oxidases activate O 2 either at the copper center or aminoquinol cofactor. Results: Catalytic intermediates from the oxidative half-reaction are structurally and spectroscopically characterized. Conclusion: The mechanism of O 2 activation may depend on accessibility dictated by two conformers of the quinone cofactor. Significance: Structural changes that inform on catalytic mechanism have been revealed in the ubiquitous copper amine oxidases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 54 publications
(55 reference statements)
1
32
0
Order By: Relevance
“…A similar decrease in the number of equatorial ligands at the copper center was observed in extended x-ray absorption fine structure studies on various dithionite-treated CAOs, in which Cu(II) is reduced to Cu(I) (64). It is therefore suggested that the tetrahedrally coordinated copper centers observed in the AGAO PEA and AGAO HTA crystals are probably in the Cu(I) oxidation state, as was proposed in a recent paper on the structure of methylamine-reduced HPAO-1 (39). Based on the full occupancy of the modeled TPQ sq in the electron density map, essentially all of their TPQ is assumed to be in the TPQ sq state.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…A similar decrease in the number of equatorial ligands at the copper center was observed in extended x-ray absorption fine structure studies on various dithionite-treated CAOs, in which Cu(II) is reduced to Cu(I) (64). It is therefore suggested that the tetrahedrally coordinated copper centers observed in the AGAO PEA and AGAO HTA crystals are probably in the Cu(I) oxidation state, as was proposed in a recent paper on the structure of methylamine-reduced HPAO-1 (39). Based on the full occupancy of the modeled TPQ sq in the electron density map, essentially all of their TPQ is assumed to be in the TPQ sq state.…”
Section: Discussionmentioning
confidence: 58%
“…An extended x-ray absorption fine structure study (64) also raised the possibility that variations in the redox potentials or the effective electron transfer distance between TPQ amr and Cu(II) may control k ET . The difference between the rate constants for AGAO determined here (Table 2; k ϩ4 ϭ 39 s Ϫ1 at 4°C, pH 6.8) and previously (k ET ϭ 73 s Ϫ1 at 5°C, pH 7.2) (37) is probably due to subtle differences in temperature and pH, both of which strongly affect the equilibrium between TPQ amr ⅐Cu(II) and TPQ sq ⅐Cu(I) (33,35,37,39,65) (Fig. 10); at higher pH values and temperatures, the equilibrium shifts toward TPQ sq ⅐Cu(I), which suggests a ⌬H value of Ͼ0 for the conformational change of TPQ.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations